2019
DOI: 10.1007/s40979-019-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

Croatian scientists’ awareness of predatory journals

Abstract: So-called predatory journals threaten to diminish the quality of papers and of scientific research. This paper defines what constitutes a predatory journal, and provides a short literature overview. The aim of the research is to explore researchers' and librarians' awareness of predatory journals, using the example of Croatia, an EU country. Several institutions control the quality of Croatian scientific journals, so there are no predatory journals in Croatia. However, Croatian scientists publish their papers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…Meanwhile, the knowledge construct showed moderate reliability as measured by test-retest reliability. The quantitative results obtained from this study were congruent with several previous findings [ 14 , 18 , 19 , 22 , 23 , [51] , [52] , [53] , [54] , [55] , [56] ]. For example, Beshyah et al indicated that less than one-third of physicians were fully aware of predatory publishing while about two-thirds of them did not know Beall's list showing that participants had low awareness of predatory journals as well as they showed that participants had varied attitudes and practices among them [54).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Meanwhile, the knowledge construct showed moderate reliability as measured by test-retest reliability. The quantitative results obtained from this study were congruent with several previous findings [ 14 , 18 , 19 , 22 , 23 , [51] , [52] , [53] , [54] , [55] , [56] ]. For example, Beshyah et al indicated that less than one-third of physicians were fully aware of predatory publishing while about two-thirds of them did not know Beall's list showing that participants had low awareness of predatory journals as well as they showed that participants had varied attitudes and practices among them [54).…”
Section: Discussionsupporting
confidence: 92%
“…This step resulted in the identification of some papers that had studied the knowledge and perceptions related to predatory journals [ 3 , 14 , 18 , 19 , 23 , [51] , [52] , [53] , [54] , [55] , [56] ]. However, most previous studies used self-administered questionnaires and varied widely in terms of questionnaire type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 16 out of the 21 participants in the qualitative phase of our study reported that they had heard about predatory journals and had some familiarity with such journals, they still published in the PPJs and did not view them as predatory. These apparent discrepancies indicate that having heard of predatory journals and knowing some of their features do not necessarily mean that authors can identify them in practice (Grgic & Guskic, 2019). Our findings contrast those of Atiso et al (2019) that Ghanaian scientists in the disciplines of animal, food, forestry and water research were aware of the differences between predatory and legitimate journals but published in them because of fast and easy publication.…”
Section: Discussionmentioning
confidence: 99%
“…The other serious factor is predatory publishing. Although researchers rarely welcome invitations from predatory journals (Nobes and Harris, 2019), they generally fail to distinguish the journals (Grgić and Guskić, 2019; Richtig et al ., 2019; Swanberg et al ., 2020). Accordingly, their proliferation may undermine the OA model and the credibility of even legitimate OA journals, and thereby endanger scholarly publishing (Eriksson and Helgesson, 2018; Dalton et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%